2017
DOI: 10.3892/ijmm.2017.3222
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-142-3p relieves neuropathic pain by targeting high mobility group box 1

Abstract: MicroRNA (miRNA) are emerging as critical regulators of neuropathic pain development. Neuroinflammation contributes to the development of neuropathic pain. miR‑142‑3p has been characterized as an inflammation‑related miRNA in various pathological processes. However, little is known about the role of miR‑142‑3p in neuroinflammation and neuropathic pain. The present study aimed to investigate the function of miR‑142‑3p in neuropathic pain by creating a murine model using spinal nerve ligation (SNL). A significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 64 publications
(78 reference statements)
0
19
0
Order By: Relevance
“…Knockdown of miR-423-5p can enhance glioma stem cells sensitivity to apigenin via regulating the mitochondrial pathway [35]. In ovarian cancer, miR-423-5p can serve as an indicator, which can repress proliferation and invasion [36]. In addition, lncRNA AFAP1-AS1 can act as a ceRNA of miR-423-5p, which can facilitate nasopharyngeal carcinoma by regulating Rho/Rac pathway [37].…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of miR-423-5p can enhance glioma stem cells sensitivity to apigenin via regulating the mitochondrial pathway [35]. In ovarian cancer, miR-423-5p can serve as an indicator, which can repress proliferation and invasion [36]. In addition, lncRNA AFAP1-AS1 can act as a ceRNA of miR-423-5p, which can facilitate nasopharyngeal carcinoma by regulating Rho/Rac pathway [37].…”
Section: Discussionmentioning
confidence: 99%
“…A significant reduction in miR-142-3p expression was observed in DRG of mice with SNL. Overexpression of miR-142-3p inhibited neuropathic pain and neuroinflammation through targeting high mobility group box 1 (HMGB1)(Zhang et al, 2018 ). This indicated that miR-142-3p may serve as a potential therapeutic target for neuropathic pain.…”
Section: Regulatory Mechanisms Of Micrornas In Chronic Painmentioning
confidence: 99%
“…In this study, we demonstrated that BDNF expression is regulated by miR-142-3p, the highly upregulated miRNA upon microglial activation, through its target CAMK2A. Several studies have shown that miR-142-3p functions as a regulator of neuroinflammation by modulating the expression of proinflammatory mediators in response to different pathological stimuli, such as multiple sclerosis, neuropathic pain, human immunodeficiency virus (HIV) and simian immunodeficiency virus encephalitis (SIVE; Chaudhuri et al, 2013;Talebi et al, 2017;Zhang et al, 2018). This study reveals a novel role of miR-142-3p in activated microglia as its upregulation upon microglial activation perturbs the CAMK2A-CREB-BDNF signaling pathway, which is involved in synaptic plasticity.…”
Section: Discussionmentioning
confidence: 89%